PROSEDUR UNDERWRITING BANCASSURANCE DAN ASURANSI JIWA SYARIAH PADA PT. ASURANSI TAKÂFUL KELUARGA - Ella Patriana; Rijal Asidiq Mulyana (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2012)
This study explains the comparative risk selection (of underwriting) in bancassurance products and Islamic life insurance products at PT. Family Takaful Insurance. The result revealed that the underwriting procedures of each product are different based on their characteristics. Full protection is designed as a simple of underwriting product only with age provisions and administrative requirements. Financing takâful products cover all financing from the bank. Thus, bank which does the insurance process will make these data as basic information about insurance customers. Since the bank is insured, and apply risk selection process as risky selection process at most insurance companies.DOI: 10.15408/aiq.v4i1.2543